MANAGEMENT TACTICS FOR PATIENTS WITH CARDIOGENIC SHOCk DUE TO ACUTE MYOCARDIAL INFARCTION: EVIDENCE BASE, AND ACTUAL PRACTICE - S. R. Giliarevsky; V. V. Rezvan; I. M. Kuzmina; P. Yu. Lopotovsky (Неотложная медицинская помощь)
ABSTRACT. The article addresses current approaches to the management of cardiogenic shock developed in patients with acute myocardial infarction. The authors present the data on the pathogenesis, clinical manifestations of this complication, and also a detailed review of current approaches to the treatment of patients with cardiogenic shock. The authors discuss causes of poor outcomes in cardiogenic shock and possible ways of the improvement.